A COMPARATIVE ANALYSIS OF SORTING ALGORITHMS - Tuhtanazarov Dilmurod Solijonovich,; Mahkamov Anvarjon Abdujabborovich,; Mukhammadiev Alisher Numonkhon ug'li, (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract: Sorting is one of the most fundamental operations in computer science, forming the backbone of countless algorithms and data processing pipelines. This paper presents a rigorous comparative study of nine canonical sorting algorithms — Bubble Sort, Selection Sort, Insertion Sort, Merge Sort, Quick Sort, Heap Sort, Counting Sort, Radix Sort, and Tim Sort — evaluating their structural design, time and space complexity, stability, adaptive behavior, and real-world applicability. Four detailed comparison tables are provided to give practitioners a concise decision reference. Our analysis demonstrates that no single algorithm universally dominates; rather, optimal selection depends on dataset size, value distribution, memory constraints, and stability requirements.